Simulasi Pencahayaan Buatan terhadap Kenyamanan Visual pada Gedung Muhammad Nu’man Somantri FPIPS - Dinda Salsabila; Amalia Tryas Putri; Naila Awalia Ramdhini; Reva Sherlyta Gusviany (Arsir: Jurnal Arsitektur, 2026)
Adequate lighting is a crucial factor in ensuring visual comfort and supporting productivity, especially in academic environments. This study aims to identify areas with insufficient artificial lighting and simulate lighting solutions using DIALux software in the corridors of the Muhammad Nu’man Somantri Building at FPIPS Universitas Pendidikan Indonesia. The research employed a qualitative descriptive method through direct observation and visual documentation. The findings indicate that corridors on floors 1 to 5 exhibit artificial lighting levels below the standards set by SNI 03-6575-2001 (350 lux for learning areas), particularly on the right side of the second-floor corridor and in areas on the third and sixth floors that lack natural lighting. The DIALux simulation demonstrates that lighting distribution can be improved through repositioning of lighting points and the use of more reflective wall colors to enhance visual comfort for building users.